Andriy Petrovych Lyabakh - Orthopedics of NAMS of Ukraine», SI «Institute of Traumatology and (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The article is dedicated to the 60th birthday of the head of the foot pathology and complex prosthetics department of the Institute of Traumatology and Orthopedics of the Academy of Medical Sciences of Ukraine, Doctor of medical sciences Professor Lyabakha A. P.